Interpreting Tempo's Perspective on the Front-Cover of Tempo Magazine March 2020 – March 2022 Regarding Covid-19 - Beni Arnold Simangunsong (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The message conveyed by a communicator through a medium must have a motive to be conveyed by the messenger. Similarly, what Tempo.co is trying to convey when providing an overview of the condition of handling Covid-19 on the front cover which shows how the handling of Covid-19 is being carried out needs to be criticized. From the 35 front covers of tempo.co magazine from March 2020 when the first case of the Covid-19 virus was discovered until April 2022 to be analyzed using the Semiotics content analysis method from Roland Barthes, this paper tries to criticize government management through public policy messages that have been carried out by the government. during the time of covid-19. The results of the study show that the Government is experiencing uncertainty, confusion, poor management, and even a dilemma in dealing with the spread of the Covid-19 virus. Tempo.co explains well the policies made by the Government which not only met resistance from businessmen, religious institutions, political parties, and even communities that were divided after the 2019 Presidential Election. However, Tempo.co also well illustrated that there is still hope for improving management. public policy in handling Covid-19 by not creating confusion in the community and hoping to improve public welfare after the endemic epidemic by working together, not blaming. each other, and unite.